Frost Multidimensional Perfectionism Scale: the portuguese version (Archives of Clinical Psychiatry, 2013)
BACKGROUND: The Frost Multidimensional Perfectionism Scale is one of the most world widely used measures of perfectionism. OBJECTIVE: To analyze the psychometric properties of the Portuguese version of the Frost Multidimensional Perfectionism Scale. METHODS: Two hundred and seventeen (178 females) students from two Portuguese Universities filled in the scale, and a subgroup (n = 166) completed a retest with a four weeks interval. RESULTS: The scale reliability was good (Cronbach alpha = .857). Corrected item-total correlations ranged from .019 to .548. The scale test-retest reliability suggested a good temporal stability with a test-retest correlation of .765. A principal component analysis with Varimax rotation was performed and based on the Scree plot, two robust factorial structures were found (four and six factors). The principal component analyses, using Monte Carlo PCA for parallel analyses confirmed the six factor solution. The concurrent validity with Hewitt and Flett MPS was high, as well as the discriminant validity of positive and negative affect (Profile of Mood Stats-POMS). DISCUSSION: The two factorial structures (of four and six dimensions) of the Portuguese version of Frost Multidimensional Perfectionism Scale replicate the results from different authors, with different samples and cultures. This suggests this scale is a robust instrument to assess perfectionism, in several clinical and research settings as well as in transcultural studies.